2020
DOI: 10.1021/acsomega.9b04142
|View full text |Cite
|
Sign up to set email alerts
|

Multispectroscopic and Computational Analysis Insight into the Interaction of Cationic Diester-Bonded Gemini Surfactants with Serine Protease α-Chymotrypsin

Abstract: Accumulation of different protein–surfactant mixtures affords further knowledge about the structure–property interactions of biomacromolecules. They will help design suitable surfactants, which, in turn, can enhance the utilization of protein–surfactant complexes in biotechnologies, cosmetics, and food industry realms. Owing to their adaptable and remarkably notable properties, we are describing herein the interaction of C m -E2O-C m gemini surfactants (m = 12, 14, and 16) with α-CHT by employing various spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…Analysis of the best-docked pose of [(Ris) (PA)]-serotonin revealed that the amino acid residues, including His182, Asn187, Asn384, Lys320, and Arg173, formed hydrogen bond interactions. In addition, Leu325, Ala321, Ala108, and Ala176 established π-alkyl interactions while Asp172 formed a halogen (fluorine) interaction [ 27 , 28 ]. The best-docked pose of [(Ris) (PA)]-dopamine revealed that the amino acid residues, including Thr142, Ala185, His393, and Tyr408, formed hydrogen bond interactions, Val115 and Phe389 established π-alkyl interactions, Trp386 established π-sigma, and Cys118 formed a halogen (fluorine) interaction [ 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the best-docked pose of [(Ris) (PA)]-serotonin revealed that the amino acid residues, including His182, Asn187, Asn384, Lys320, and Arg173, formed hydrogen bond interactions. In addition, Leu325, Ala321, Ala108, and Ala176 established π-alkyl interactions while Asp172 formed a halogen (fluorine) interaction [ 27 , 28 ]. The best-docked pose of [(Ris) (PA)]-dopamine revealed that the amino acid residues, including Thr142, Ala185, His393, and Tyr408, formed hydrogen bond interactions, Val115 and Phe389 established π-alkyl interactions, Trp386 established π-sigma, and Cys118 formed a halogen (fluorine) interaction [ 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 5 a, CT complex [(HPL)(TCNQ)] with dopamine (CTtD) revealed that the amino acid residues, including His393, Ser193, and Tyr416, formed hydrogen bond interactions. Additionally, Val91 and Trp413 (π-Alkyl); Tyr408 (π-π T-Shaped); Cys118 (π-Alkyl); Thr412 and Leu94 (π-Sigma); and Asp114 (Attractive charge) interactions were present [ 15 , 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…The Coats-Readfern and Horowitez-Metzegar methods [ 55 , 56 ] were used to collect the kinetic thermodynamic data of the maximal DTG peak decomposition steps of all charge–transfer complexes. The kinetic parameters, E , A , Δ S , Δ H , Δ G , and r were calculated, and the data are listed in Table 1 and displayed in Figure 4 .…”
Section: Resultsmentioning
confidence: 99%